Healing Potential of Single Dose of Inactivated Autologous PRP, Laser, and PRP/Laser Combination on Full-Thickness Skin Defect in Dogs - Haithem Farghali; Shaaban Gadallah; Tarik Misk; Ibrahim Emam; Naglaa Abd ElKader; Marwa Khattab; Huda Abubakr; Abdelrhman Elsabaa; Amal Hammad (Iranian Journal of Veterinary Surgery, 2024)
It is worth considering the regenerative capacity of platelet-rich plasma (PRP) and laser for challenging skin wounds. Therefore, this study aimed to investigate the healing potential of a single dose of inactivated autologous PRP, Laser, and PRP/Laser on full-thickness skin defects in dogs. Three mongrel dogs were subjected to 4 circular full-thickness skin defects on the thoracic region. Hence, 4 groups were evaluated: The control group (conventional treatment); the PRP group (single subcutaneous infiltration of inactivated autologous PRP); the laser group (laser for one session), and the PRP/laser group (single subcutaneous infiltration of autologous PRP followed by laser for one session). Measured variables were the percentage of wound size, catalase activity, malondialdehyde concentration, and expression of vascular endothelial growth factor A and collagen I alpha 2 genes. Tissue biopsies were also harvested for histopathologic and immunohistochemistry assessments. The percentage of wound size was significantly lower in all groups than in the control group with a greater reduction in the PRP group. Histopathologic findings were better in PRP and PRP/laser groups with superiority for PRP. Other variables were significantly different among groups at some time points. In conclusion, PRP has a greater potential than laser and PRP/laser for accelerating and improving the quality of healing of acute full-thickness skin wounds in dogs.